PROFIL PENGGUNAAN DANA PERUM PEGADAIAN OLEH NASABAH DI KABUPATEN SUMBA TIMUR - Karolina A. Rewa; Anastasia Diana M. Tumimomor (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
One type of financial institution that is widely used by the wider community, especially the lower middle class in East Sumba Regency is Perum Pegadaian. In general, customers make use of pawnshop services for various urgent needs, so that the alternative to get cash as soon as possible is through the pawnshop by bringing collateral. The results showed that the majority of mortgage customers using borrowed funds were used to meet various consumer needs, both for daily needs and for children's educational needs. And only a handful of customers pawned goods for business needs. This means that pawnshop services are used by customers to meet immediate consumer needs.